A Novel Tobacco Use Phenotype Suggests the 15q25 and 19q13 Loci May be Differentially Associated With Cigarettes per Day and Tobacco-Related Problems. Issue 4 (17th October 2016) - Richmond-Rakerd, Leah S.; Otto, Jacqueline M.; Slutske, Wendy S.; Ehlers, Cindy L.; Wilhelmsen, Kirk C.; Gizer, Ian R.
Abstract: Introduction: Tobacco use is associated with variation at the 15q25 gene cluster and the cytochrome P450 (CYP) genes CYP2A6 and CYP2B6. Despite the variety of outcomes associated with these genes, few studies have adopted a data-driven approach to defining tobacco use phenotypes for genetic association analyses. We used factor analysis to generate a tobacco use measure, explored its incremental validity over a simple indicator of tobacco involvement: cigarettes per day (CPD), and tested both phenotypes in a genetic association study. Methods: Data were from the University of California, San Francisco Family Alcoholism Study ( n = 1942) and a Native American sample ( n = 255). Factor analyses employed a broad array of tobacco use variables to establish the candidate phenotype. Subsequently, we conducted tests for association with variants in the nicotinic acetylcholine receptor and CYP genes. We explored associations with CPD and our measure. We then examined whether the variants most strongly associated with our measure remained associated after controlling for CPD. Results: Analyses identified one factor that captured tobacco-related problems. Variants at 15q25 were significantly associated with CPD after multiple testing correction (rs938682: p = .00002, rs1051730: p = .0003, rs16969968: p = .0003). No significant associations were obtained with the tobacco use phenotype; however, suggestive associations were observed for variants in CYP2B6 near CYP2A6 (rs45482602: p s = .0082, .0075) and CYP4Z2P (rs10749865: p s = .0098, .0079). Conclusions: CPD captures variation at 15q25. Although strong conclusions cannot be drawn, these finding suggest measuring additional dimensions of problems may detect genetic variation not accounted for by smoking quantity. Replication in independent samples will help further refine phenotype definition efforts. Implications: Different facets of tobacco-related problems may index unique genetic risk. CPD, a simple measure of tobacco consumption, is associated with variants at the 15q25 gene cluster. Additional dimensions of tobacco problems may help to capture variation at 19q13. Results demonstrate the utility of adopting a data-driven approach to defining phenotypes for genetic association studies of tobacco involvement and provide results that can inform replication efforts.